The Role of Propolis in Pulp Pain by Inhibiting Cyclooxygenase-2 Expression - Ira Widjiastuti; Widya Saraswati; Annisa Rahma (Universitas Airlangga, 2021)
Background: Inflammation of the pulp can lead to elicit pain. Pain in inflammation is induced by the cyclooxygenase-2 enzyme (COX-2) which induces prostaglandin E2 (PGE2) resulting in pain. Pain in the pulp can be relieved by eugenol. In its application, eugenol is toxic to pulp fibroblasts. Due to the side effect, it is worth considering other biocompatible materials with minimal side effects, such as propolis. Flavonoids and phenolic acids that contained in propolis can inhibit COX-2. Therefore, an analysis outlined in the literature review is needed to examine the results of research related to the role of propolis as pulp pain relief by inhibiting COX-2 expression. Purpose: To analyze the role of propolis in pulp pain by inhibiting COX-2 expression. Reviews: Propolis extract that extracted by ethanol, water, and hydroalcohol has pain relief properties in the pulp by inhibiting COX-2 by directly binding to the COX-2 receptors and by reducing the production of proinflammatory cytokines which are COX-2 inducers, proven through in vivo, in vitro, and in silico studies in various target cell organs. Conclusion: Propolis extract has high prospect as inflammatory pain inhibitor in the pulp by inhibit COX-2 expression.